2017
DOI: 10.1590/1413-81232017221.20532015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores associados à utilização de serviços públicos de saúde por homens adultos

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
2
5
0
11
Order By: Relevance
“…It is worth mentioning some characteristics of the men presented here that resemble that found in a study conducted in health facilities in Rio Grande do Norte, where it was evidenced that the users had mean age of 40 years, most of them were brown, ingested alcohol and did not use cigarettes 12 . In addition, a household survey conducted in 2013 with adults living in Maringá, Paraná, showed that most of the educated men had more than eight years of schooling and had work at the time 13 .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning some characteristics of the men presented here that resemble that found in a study conducted in health facilities in Rio Grande do Norte, where it was evidenced that the users had mean age of 40 years, most of them were brown, ingested alcohol and did not use cigarettes 12 . In addition, a household survey conducted in 2013 with adults living in Maringá, Paraná, showed that most of the educated men had more than eight years of schooling and had work at the time 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The studies found on this theme defined the dependent variable by using a single question, such as: “When did you last go to any health service?” [32]; “What type of health service do you use most often in terms of management/financing?” [13]; “Number of consultations with health professionals in the last 12 months” [33]; “Have you consulted professionals (for example, doctors, psychotherapists) for depressive symptoms?” [34], among others, which did not address the phenomenon in its totality and complexity, as investigated in this study through LCA.…”
Section: Discussionmentioning
confidence: 99%
“…Isso pode ter relação com quem tem maior poder aquisitivo, que tem possibilidade de contratar planos de saúde particulares, diminuindo a frequência da busca aos serviços das UAPS (2) . Em suma, a condição socioeconômica e o nível de escolaridade podem definir a busca por serviços de APS, e possível adoção de comportamentos saudáveis (9) .…”
Section: Discussionunclassified
“…Nesse sentido, no que se refere aos julgamentos e às praxes dos homens no processo saúde-doença, os padrões básicos determinados pela sociedade e a construção do gênero impactam negativamente ao acesso à saúde dessa população (6)(7)(8) . Isso porque o modelo de masculinidade está intrinsicamente relacionado à falta de atenção e de preocupação com o próprio estado de higidez, e isso repercute no surgimento e perpetuação dos fatores de risco de adoecimento da população masculina (6,(9)(10) .…”
Section: Introductionunclassified